2023
DOI: 10.1039/d3cp00489a
|View full text |Cite
|
Sign up to set email alerts
|

Diamondoid ether clusters in helium nanodroplets

Abstract: Diamondoid ethers were introduced into superfluid helium nanodroplets and the resulting clusters were analyzed by time-of-flight mass spectrometry. Clusters of higher abundances (magic number clusters) were identified and the corresponding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In previous studies of self-organized HND aggregates consisting of diamondoid molecules such as adamantane, [20][21][22] diamantane 23 and diamondoid ethers, 24 certain preferences for cluster abundances were found that belonged to particularly stable geometries. These observed privileged abundances were termed as magic numbers.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…In previous studies of self-organized HND aggregates consisting of diamondoid molecules such as adamantane, [20][21][22] diamantane 23 and diamondoid ethers, 24 certain preferences for cluster abundances were found that belonged to particularly stable geometries. These observed privileged abundances were termed as magic numbers.…”
Section: Resultsmentioning
confidence: 96%
“…S3, ESI†). Building on our previous benchmarking for similar systems, 23,24 we performed a search for viable cluster structures using CREST based on the GFN methods, 36,37 more specifically, by applying the iterative meta -dynamic sampling for non-covalently bound systems (NCI-iMTD mode). After identifying the best candidates, we performed single point computations on these geometries using the B3LYP-gCP-D3(BJ)-ABC/def2-TZVPP level of theory.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations